Impact of a Copper-Infused Countertop Material on the Bacterial Surface Burden: Results of a Field and Laboratory Study. (4th October 2017) - Braden, Amy; Roach, Linda; Stehle, John; Anderson, Andrea; Bischoff, Werner
Abstract: Background: Antimicrobial surfaces have become a promising technology of integrating additional safeguards into hospitals' fight against Healthcare Associated Infections (HAIs). This study assesses the potential benefits of copper-infused countertops compared with standard, laminated surfaces. Methods: The efficacy of a novel surface material in reducing the bacterial load was tested in a Neuro ICU (copper surface, intervention) and a Surgical ICU (laminated surface, control) during routine care (field test). Surfaces were cleaned following standard hospital protocol. After bleach cleaning of 5 high touch areas, pre-moistened swab samples were taken immediately, at 2 hours, and at 4 hours, for a total of 680 surface samples in 46 patient rooms. After incubation on blood agar plates, colony forming units (CFU) were documented. In a separate laboratory test, copper and laminated surfaces were inoculated with S . A ureus and the bacterial load was measured as described. Pre-treatment of the copper counter top followed manufacturer recommendation (light buffing with 365 grit sandpaper every 24 hours) or hospital-approved disinfection policy. Count numbers at the different time points for the surfaces were analyzed. Results: In the field test, no statistically significant differences in bacterial surface burden were noted between the intervention and control unit at the three time points (RR = 1.6 (0.5–5.0); P = 0.4210). In the lab test, significant reductions in CFU across all surfaces were observed after 2 hours (>50%; P < 0.05). Light buffing led to the highest reduction in CFU (>99%; P < 0.05). After 4 hours the laminated surface showed further significant reduction (>93%; P < 0.05). However, CFU on the copper surface treated with standard disinfectant did not change ( P <  0.05). Conclusion: The copper surface significantly reduces the bacterial burden if reactivated by light buffing with sandpaper in a lab test. Not following manufacturer recommendation will lead to similar (field) or even higher bacterial burden (lab) compared with standard laminated surfaces. Before implementation, considerations should be given to the increased workload due to daily surface reactivation, the potential of fine particle exposure, and the higher product costs. Disclosures: All authors: No reported disclosures.